Analytical evaluation of damage probability matrices for hill-side RC buildings using different seismic intensity measures. (15th March 2020) - Surana, Mitesh; Meslem, Abdelghani; Singh, Yogendra; Lang, Dominik H.
Highlights: Damage probability matrices for hill-side buildings designed for different code levels. Effect of irregular configurations of hill-side buildings explored. Different intensity measures considered. Need highlighted to include these parameters in the next-generation ELE studies. Abstract: In the present study seismic response and vulnerability of hill-side RC buildings, often observed in the Indian Himalayan region as well as in some other parts of the world were analytically investigated using non-linear dynamic analyses. The conducted analyses led to the development of seismic fragility functions based on three different ground-motion intensity measures, viz. peak ground acceleration, spectral acceleration at the fundamental building period, and average spectral accelerations over a range of periods. In addition to the different code design levels that are considered in the assessment, the choice of the ground-motion intensity measure as well as the structural configuration type of these hill-side buildings show quite significant effects on the resulted damage probabilities of different damage states, and thus on the computed mean damage ratio. The peak ground acceleration results in a significant overestimation of the mean damage ratio for the maximum considered earthquake hazard level when compared with the spectral acceleration-based intensity measures. On the other hand, the irregular structural configuration of hill-side buildings alone results in a significantly higher mean damage ratio when compared with regular structural configuration. In addition to the design code level, the need to incorporate both of these effects, i.e. the choice of ground-motion intensity measure and irregular structural configurations of hill-side buildings, in the next generation of earthquake loss estimation studies and software tools is underlined.